Outpatient Pain Management in Children With Chronic Pancreatitis: A Scoping Systematic Review. Issue 2 (February 2022) - Perito, Emily R.; Pohl, John F.; Bakker, Caitlin; Armfield, Matthew A.; Barth, Bradley; Cuneo, Addison; Mascarenhas, Maria; Mehta, Megha; Schwarzenberg, Sarah Jane
Abstract : Objectives: Although pain management is central to pediatric chronic pancreatitis (CP) care, no evidence-based guidelines exist. In this scoping systematic review, we sought promising strategies for CP pain treatment in children. Methods: We systematically reviewed literature on pain management in children and adults with CP, and 2 conditions with similar pain courses: juvenile idiopathic arthritis and sickle cell disease. Results: Of 8997 studies identified, 287 met inclusion criteria. There are no published studies of analgesic medications, antioxidants, dietary modification, integrative medicine, or regional nerve blocks in children with CP. In adults with CP, studies of nonopioid analgesics, pancreatic enzymes, and dietary interventions have mixed results. Retrospective studies suggest that endoscopic retrograde cholangiopancreatography and surgical procedures, most durably total pancreatectomy with islet autotransplant, improve pain for children with CP. Follow-up was short relative to a child's life. Large studies in adults also suggest benefit from endoscopic therapy and surgery, but lack conclusive evidence about optimal procedure or timing. Studies on other painful pediatric chronic illnesses revealed little generalizable to children with CP. Conclusions: No therapy had sufficient high-quality studies to warrant untempered, evidence-based support for use in children with CP. Multicenter studies are needed to identify pain management "best practices."